Artificial radio lighting with sources of microwave dynamic chaos - Dmitriev, A S; Efremova, E V; Ryzhov, A I; Petrosyan, M M; Itskov, V V (Chaos (Woodbury, N.Y.), 2021)
Application of dynamic chaos for the illumination of the surrounding space by artificial incoherent sources of microwave radiation with the purpose of its subsequent observation using special receiving equipment is considered. An incoherent broadband microwave radiation field is provided by "radio light lamps" based on dynamic chaos generators. The radio light is received with specially designed sensitive elements that combine the properties of an envelope detector in communication systems and a radiometer. It is shown that with the help of directional antennas connected to these sensitive elements, it is possible to create receivers with spatial resolution for visualizing a part of the surrounding space in artificial radio light. Radio light images of a room have been obtained. The possibility to detect changes associated with the emergence of new objects on these images is demonstrated.